Psoriasis, psoriatic arthritis and risk of gout in US men and women. Issue 8 (20th March 2014) - Merola, Joseph F; Wu, Shaowei; Han, Jiali; Choi, Hyon K; Qureshi, Abrar A
Abstract : Background and objective: Individuals with psoriasis have increased blood levels of uric acid. However, there is no prospective data on the association between psoriasis and uric acid levels and subsequent development of gout. In this study, we examined the risk of gout among individuals with psoriasis and psoriatic arthritis (PsA) in two cohorts of men and women, the Health Professionals Follow-up Study (HPFS) (1986–2010) and Nurses' Health Study (NHS) (1998–2010). Methods: 27 751 men and 71 059 women were included in the analysis. Lifetime history of physician-diagnosed incident psoriasis and PsA was confirmed by validated supplementary questionnaires. Incident gout diagnoses were confirmed based on the American College of Rheumatology survey criteria. We used Cox proportional hazards models controlling for potential risk factors to calculate the HRs with 95% CIs of incident gout while simultaneously adjusting for several common risk factors. Results: We documented 2217 incident cases of gout during follow-up. Psoriasis was associated with an increased risk of subsequent gout with a multivariate HR of 1.71 (95% CI 1.36 to 2.15) in the pooled analysis. Risk of gout was substantially augmented among those with psoriasis and concomitant PsA (pooled multivariate HR: 4.95, 95% CI 2.72 to 9.01) when compared to participants without psoriasis. Conclusions: In this prospective study of US women and men, psoriasis and PsA were associated with an increased risk of gout.